2021
DOI: 10.3389/fphar.2021.766909
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Lapachone Attenuates BMSC-Mediated Neuroblastoma Malignant Transformation by Inhibiting Gal-3/Gal-3BP/IL6 Axis

Abstract: The inflammatory factor IL6 secreted by bone marrow mesenchymal stem cells (BMSCs) in the tumor microenvironment (TME) facilitates the survival and therapeutic resistance of neuroblastoma (NB). Here, we found that IL6 expression in primary tumor tissues or bone marrow (BM) metastases was closely associated with the disease risk and prognosis of NB patients. IL6 secretion from immortalized BMSC (iBMSC) was directly regulated by NB cells and is involved in promoting the proliferation and metastasis of NB cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The administration of β-LAP is logical if it does not interfere with the anticancer effects of DOX. Several studies have shown promising antitumor activity of β-LAP against various tumor types, particularly neuroblastoma, [42] breast cancer, [43] melanoma, [44] oral squamous cell carcinoma, [45] and so forth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The administration of β-LAP is logical if it does not interfere with the anticancer effects of DOX. Several studies have shown promising antitumor activity of β-LAP against various tumor types, particularly neuroblastoma, [42] breast cancer, [43] melanoma, [44] oral squamous cell carcinoma, [45] and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of β‐LAP is logical if it does not interfere with the anticancer effects of DOX. Several studies have shown promising antitumor activity of β‐LAP against various tumor types, particularly neuroblastoma, [ 42 ] breast cancer, [ 43 ] melanoma, [ 44 ] oral squamous cell carcinoma, [ 45 ] and so forth. Taken together, our results demonstrate that β‐LAP not only suppresses NF‐kB signaling pathway but also activates Nrf2 signaling pathway via modulation of NAD + /SIRT‐1/FXR/AMPK axis.…”
Section: Discussionmentioning
confidence: 99%
“…Cell transfection was carried out according to our published research ( Zhou Y. et al, 2021 ). Briefly, for gene silencing of miR-204-5p or overexpression of human FLIP and H19, miRNA inhibitor or plasmid carrying the corresponding sequence were purchased from Genepharma (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…As an essential component of TME, the ECM is known to be a dense network with structural proteins, bridging proteins, proteoglycans and enzymes that mainly provide biochemical and structural support for tumorigenesis and progression ( Ho et al, 2020 ; Gonzalez-Molina et al, 2022 ; Jiang et al, 2022 ). Various chemokines, inflammatory factors, cytokines and growth factors secreted from TME-associated inflammatory cells or stromal cells collectively constitute a dynamic microhabitat possessing diverse functional states through crosstalk with the ECM ( Wohlrab et al, 2014 ; Zhou et al, 2021 ). The aberrantly overexpressed ECM components in TME appear to be associated with stronger pro-invasive, pro-metastatic and pro-proliferative capacities of NB.…”
Section: Nanotechnology Enhances Therapeutic Treatment For Neuroblastomamentioning
confidence: 99%